2001
DOI: 10.4049/jimmunol.167.8.4560
|View full text |Cite
|
Sign up to set email alerts
|

A Dual-Function DNA Vaccine Encoding Carcinoembryonic Antigen and CD40 Ligand Trimer Induces T Cell-Mediated Protective Immunity Against Colon Cancer in Carcinoembryonic Antigen-Transgenic Mice

Abstract: A carcinoembryonic Ag (CEA)-based DNA vaccine encoding both CEA and CD40 ligand trimer achieved effective tumor-protective immunity against murine colon carcinoma in CEA-transgenic mice by activating both naive T cells and dendritic cells. Peripheral T cell tolerance to CEA was broken in a prophylactic model by this novel, dual-function DNA vaccine, whose efficacy was further enhanced by boosts with a recombinant Ab-IL-2 fusion protein (huKS1/4-IL-2). These conclusions are supported by four lines of evidence. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
51
2

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(55 citation statements)
references
References 33 publications
2
51
2
Order By: Relevance
“…Considering the previous studies that demonstrated a potent adjuvant activity of the CD40L gene for inducing protective immunity against Leishmania major infection and tumors (9,10), our present results indicating no significant effects of pCD40L were somewhat unexpected. However, this discrepancy may be explained by a difference in the construction of CD40L used for those studies.…”
Section: Discussioncontrasting
confidence: 43%
“…Considering the previous studies that demonstrated a potent adjuvant activity of the CD40L gene for inducing protective immunity against Leishmania major infection and tumors (9,10), our present results indicating no significant effects of pCD40L were somewhat unexpected. However, this discrepancy may be explained by a difference in the construction of CD40L used for those studies.…”
Section: Discussioncontrasting
confidence: 43%
“…As a result of the upregulation of costimulatory molecules (51,58), the APCs are activated, the CD4 ϩ -T-cell responses are augmented by increased cytokine production (10), and CD4-dependent naïve CD8 ϩ T cells are activated in vivo (44). Genetic fusion of CD40L to DNA vaccines was demonstrated to be effective in enhancing the cellular immune responses to a vaccine antigen (11,55).…”
mentioning
confidence: 99%
“…The association of specific adjuvants and DNA vaccination has been extensively investigated (11,21,25,37). Some studies demonstrated that co-administration of plasmids encoding cytokine genes as adjuvants significantly enhanced immune response.…”
mentioning
confidence: 99%